Common institutional ownership and stock price crash risk - Chen, Shenglan; Ma, Hui; Wu, Qiang; Zhang, Hao (Contemporary Accounting Research, 2024)
Abstract This paper presents new evidence on the economic benefits arising from common institutional ownership. We find a negative and significant effect of common institutional ownership on stock price crash risk. This effect is robust to a battery of robustness checks and is causal according to some identification tests, including difference‐in‐differences analyses on financial institution mergers. We find evidence that the negative effect is attributable to the monitoring role of common institutional owners—a role that is enabled by common owners' lower information processing cost and greater monitoring incentives owing to governance externalities. We also find that common owners negatively influence crash risk through constraining bad news hoarding and that common owners are more likely to force CEO turnover when a firm has higher crash risk. Overall, our results suggest that common institutional shareholders play a unique and effective monitoring role that fends off stock price crashes.